Alnôbakskwak: Native American Women Making Ceremonial Regalia - Sheehan, Vera Longtoe (DigitalCommons@University of Nebraska - Lincoln, 2020)
In the borderland between the United States and Canada stand communities of Native American people whose resilience enabled them to survive the ravages of hundreds of years of wars, eugenics, and racism that persists into the present day. These factors contributed to the decline of traditions and a subsequent period of cultural renewal and pride that has led up to several Abenaki tribes petitioning the State of Vermont for tribal Recognition. When the Recognition applications were compared, it became apparent that they had retained many of their agricultural traditions and that their cultural revitalization efforts could be extended not only to their ceremonial dances but also to the creation of ceremonial regalia for both their planting and harvest ceremonies. The complementary nature of regalia would help strengthen their community and restore cultural context to the dances for the first time in generations. As women from different communities prepared for the renewal of the harvest dances, questions arose around cultural identity, design motifs, materials, and the possession of the ceremonial regalia. This paper is a retelling of the process that led to creating the ceremonial garments and a description of outcomes. It sets the stage for a discussion about the essential hidden leadership roles of Native American women in consensus-based society and demonstrates how a team of Abenaki women from different communities played a crucial role in the cultural revitalization process through the creation and usage of regalia for the agricultural ceremony.